Quantitative analysis of cornea endothelial cell damage from enucleation, corneal buttoning, and storage in donor corneas using trypan blue dye staining. Issue 36 (9th September 2022) - Yoon, Young Chae; Byun, Yong-Soo; Kim, Patrick; Ha, Min Ji; Whang, Woong Joo; Na, Kyung Sun; Kim, Eun Chul; Kim, Hyun Seung; Hwang, Ho Sik
Abstract : We aimed to quantitatively analyze the corneal endothelial cell damage by measuring the area stained with trypan blue dye, and to confirm the degree of corneal endothelial cell damage resulting from enucleation, corneal buttoning, and storage in donor corneas intended for use in human corneal transplantation. This study was a retrospective analysis of medical records and videos recorded during keratoplasty. Twenty-one corneal buttons of 21 donors that underwent endothelial cell staining using trypan blue for the donor preparation during DALK or DMEK were included in the study. The percentage of stained area in entire corneal endothelia and the percentage of the stained area in the 8-mm diameter circle were quantitatively analyzed using Adobe Photoshop. The mean percentage of the stained area in the entire corneal endothelia in 13 corneas was 8.1 ± 13.3% (range, 0.0–56.1%), and the mean percentage of the stained area in a circle with a diameter of 8 mm in 21 corneas was 3.4 ± 5.2% (range, 0.0–18.9%). The correlations between the death-to-preservation time, the training duration of the residents who performed donor corneal buttoning, and the percentage of the stained area in the 8-mm diameter circle were not significant( P = .441, P = .495, respectively). Cornea thickness and endothelial cell density did not differ between 10 eyes in the group with the percentage of the stained area in a circle with a diameter of 8 mm <5% and 5 eyes in the group with the percentage more than 5% damage ( P = .854, P = .358). The corneal endothelial cell damage could be quantitatively analyzed using trypan blue staining before keratoplasty in donor cornea. The amount of corneal endothelial cell damage in the central 8-mm circle was mostly acceptable, but some cases showed significantly severe endothelial cell damage. The corneal thickness and endothelial cell density did not differ between 10 eyes in the group with the percentage of the stained area in a circle with a diameter of 8 mm <5% and 5 eyes in the group with the percentage more than 5% damage. Therefore, pachymetry and specular microscopy are not sufficient for evaluating donor corneas before keratoplasty.